PENGARUH PEMBERIAN EKSTRAK DAUN BELIMBING WULUH (Averrhoa blimbi L.) DAN DAUN JARAK PAGAR (Jatropha curcas L.) TERHADAP KADAR GLUKOSA MENCIT (Mus musculus L.) - Nurhayu Malik; Nasaruddin Nasaruddin; Fitmayanti Fitmayanti (Universitas Halu Oleo, 2022)
This study aimed to determine the effect of giving starfruit leaf extract and Jatropha leaf extract, a mixture of starfruit leaf extract and Jatropha leaf extract and glucobay drug (Acarbose) on glucose levels of mice. A total of 20 mice weighing 20-30 grams aged 2-3 months were divided into 5 treatment groups namely K0 as a 5% glucose control, K1 (5% glucose solution and glucobay drug), K2 (5% glucose solution and leaf extract starfruit wuluh), K3 (5% glucose solution and Jatropha leaf extract) and K4 (5% glucose solution, a mixture of starfruit leaf extract and Jatropha leaves). Mice were first measured initial glucose levels. Giving 5% glucose solution, carried out for 14 days so as to reach the condition of hyperglycemia. Treated with starfruit leaf extract, jatropha leaf extract and a mixture of starfruit leaf extract and jatropha leaves with the same dose that is 400 mg / gr BW, administering synthetic drug glucobay with a dose of 6.5 mg / gr BB for 14 days and calculated final glucose level. The results showed that the administration of starfruit leaf extract and Jatropha leaf extract, the mixture of Wuluh starfruit leaf extract and Jatropha leaf extract and glucobay drug influenced the treatment group. Based on the analysis using the LSD test (α = 0.05) significantly different in the F test (ANOVA). In the LSD test in the treatment (K1, K2, K3 and K4) decreased compared to K0 as glucose control. The highest reduction in glucose levels was found in the K3 treatment (70 mg / dL).